ON THE SPECIFICITY OF THE ONLINE NEWS LANGUAGE (ON THE MATERIAL OF UZBEKISTAN AND RUSSIAN MEDIA) - Ahmedova, Malika (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article examines the features of presenting Internet news in Uzbek (kun.uz, gazeta.uz, podrobno.uz) and Russian (gazeta.ru, lenta.ru) media according to the specifics of headlines and leads, as well as their length, paragraph size, number of sentences in a paragraph, number of words in sentences, number of letters in words. The results of the calculations showed that the indicated parameters of the Uzbek media generally exceed the parameters of the Russian media, which can be explained by the desire for a more detailed presentation of news. The study also showed that in all publications, exceptlenta.ru, simple twopart sentences with direct word order are used in the headings, excluding communication between the author and the reader. In lenta.ru,headings with inversion in a simple sentence prevail, and one-component sentences are used to fulfill a certain intention of the author.
Keywords: Internet news; title; lead; the length of the title; leadparagraph; number of words in sentences